Implementation of Multicultural Education in Primary Schools to Build Intercultural Tolerance: A Case Study on Escola Primaria Timor-Leste: Implementation of Multicultural Education in Primary Schools - Agus Martins; Ana Joana dos Reis (Creative Smart Visionary, 2025)
This study aims to explore the implementation of multicultural education at Escola Primaria 05 de Beloi, Timor-Leste, focusing on the challenges faced by teachers and their impact on students. Using a qualitative approach with in-depth interviews, this study involved 8 teachers as respondents. The results show that teachers have varying understandings of multicultural education, with the majority only introducing cultural diversity through materials such as folk tales and discussions. The main challenges faced are limited resources and teaching materials that do not cover diversity comprehensively. Nevertheless, the implementation of multicultural education is beginning to show positive impacts, with students becoming more open to cultural differences. These findings indicate the need for a more experience-based approach and the development of more inclusive teaching materials. The implications of this study are the importance of further training for teachers and the provision of resources that support more effective and sustainable multicultural teaching.